Effect of Financial Report Quality and Accounting Systems on MSME Performance with HR Competence - Rizky Mulyani, Ulva; Rizki Salisa, Naila; Wazzar Achmad, Affan (EAJ (Economic and Accounting Journal), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in regional economic development, particularly in areas such as Kudus Regency, where they serve as a backbone of local industry and employment. However, their performance is often constrained by limited financial management practices and a lack of competent human resources. This study examines the effect of financial statement quality and accounting system usage on the performance of MSMEs, with human resource competency as a moderating variable. Using a quantitative approach, data were collected through questionnaires from MSME actors in Kudus Regency, selected via simple random sampling. The analysis employed Moderated Regression Analysis (MRA). Results reveal that financial statement quality has a negative and insignificant effect on MSME performance, while accounting system usage has a positive and significant effect. Furthermore, human resource competency positively moderates the relationships between both financial statement quality and accounting system usage with MSME performance.